Quasi-Brittle Fracture Modeling of Preflawed Bitumen Using a Diffuse Interface Model - Yue Hou; Fengyan Sun; Wenjuan Sun; Meng Guo; Chao Xing; Jiangfeng Wu (Advances in Materials Science and Engineering)
Fundamental understandings on the bitumen fracture mechanism are vital to improve the mixture design of asphalt concrete. In this paper, a diffuse interface model, namely, phase-field method is used for modeling the quasi-brittle fracture in bitumen. This method describes the microstructure using a phase-field variable which assumes one in the intact solid and negative one in the crack region. Only the elastic energy will directly contribute to cracking. To account for the growth of cracks, a nonconserved Allen-Cahn equation is adopted to evolve the phase-field variable. Numerical simulations of fracture are performed in bituminous materials with the consideration of quasi-brittle properties. It is found that the simulation results agree well with classic fracture mechanics.